2016
DOI: 10.1212/wnl.0000000000003318
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide survey of pediatric acquired demyelinating syndromes in Japan

Abstract: Objective:To investigate the clinical and epidemiologic features of pediatric acquired demyelinating syndromes (ADS) of the CNS in Japan.Methods:We conducted a nationwide survey and collected clinical data on children with ADS aged 15 years or younger, who visited hospitals between 2005 and 2007.Results:Among 977 hospitals enrolled, 723 (74.0%) responded to our inquiries and reported a total of 439 patients as follows: 244 with acute disseminated encephalomyelitis (ADEM), 117 with multiple sclerosis (MS), 14 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 35 publications
3
36
3
Order By: Relevance
“…Relapsing cases were assigned the following diagnostic categories: (1) multiple sclerosis, fulfilling the 2013 International Pediatric Multiple Sclerosis Study Group consensus criteria and the 2010 revised McDonald criteria; (2) NMOSD, fulfilling the 2015 Wingerchuk criteria; (3) multiphasic disseminated encephalomyelitis and ADEM‐optic neuritis fulfilling the 2013 International Pediatric Multiple Sclerosis Study Group consensus criteria; and (4) recurrent demyelination in a single central nervous system (CNS) area without evidence of clinically silent disease (for example relapsing optic neuritis).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relapsing cases were assigned the following diagnostic categories: (1) multiple sclerosis, fulfilling the 2013 International Pediatric Multiple Sclerosis Study Group consensus criteria and the 2010 revised McDonald criteria; (2) NMOSD, fulfilling the 2015 Wingerchuk criteria; (3) multiphasic disseminated encephalomyelitis and ADEM‐optic neuritis fulfilling the 2013 International Pediatric Multiple Sclerosis Study Group consensus criteria; and (4) recurrent demyelination in a single central nervous system (CNS) area without evidence of clinically silent disease (for example relapsing optic neuritis).…”
Section: Methodsmentioning
confidence: 99%
“…Two studies looking at the prevalence of AQP4‐Ab in paediatric patients presenting with a first episode of demyelination have identified these in only 0.7% (2/279) to 4.5% (3/64) of children, which may reflect the rarity of NMOSD in certain populations. A recent nationwide study of Japanese children identified AQP4‐Ab in 1 out of 12 patients with multiple sclerosis and three out of six patients with NMOSD who were tested . Nevertheless, the severity of NMOSD and the role for specific therapies prompts testing for AQP4‐Ab in all children with ADS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to numerous studies carried out in NorthAmerica and Europe, recent studies have been published on pediatric cohorts of selected populations (Hispanic North-Americans) [9] or from other countries such as Turkey, Kuwait, Iran, Brazil, Marroch, Korea and Japan [10][11][12][13][14][15][16][17], indicating an increased interest in this area of clinical research. Many papers have been recently published giving a better definition of incidence, clinical aspects, pathophysiology, immunology, neuroimaging and treatment: a summary of these studies is provided by a recent publication of the International Pediatric MS Study Group [18].…”
Section: Introductionmentioning
confidence: 99%
“…ADEM is a demyelinating disorder of the CNS with an estimated annual incidence of 0.23 to 0.4 of 100,000 children. [8][9][10][11] In 2007 the International Pediatric Multiple Sclerosis Society Group (IPMSSG) published consensus definitions for demyelinating disorders of childhood, including ADEM, 12 which was updated in 2013. 13 The clinical presentation has reportedly a latent period between anteceding viral infection and onset of symptoms of approximately 12 days, 14,15 during which prodromal symptoms can include fever, malaise, headache, nausea, and vomiting progressing to encephalopathy and coma.…”
Section: Discussionmentioning
confidence: 99%